Pengambilan Keputusan Partisipatif Kepala Madrasah Aliyah Negeri Tanjung Balai Sumatera Utara Dalam Meningkatkan Mutu Pendidikan - Apriyani Apriyani; Mujamil Qomar; As’aril Muhajir; Prim Masrokan Mutohar; Sulistiyorini Sulistiyorini (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims at the madrasah principal's policy in making participatory decisions in improving the quality of education, namely; (1) The process of participatory decision-making of the madrasah principal in improving the quality of education, (2) Implementation of participatory decision-making of the madrasah principal in improving the quality of education, (3) Evaluation of participatory decision-making of the madrasah principal in improving the quality of education. This research method uses a qualitative approach with a field type that is carried out directly on the object to obtain data and share information through observation, documentation and interviews. This study provides results that; (1) The process of participatory decision-making in improving the quality of education begins with the identification of problems that have been collected based on facts and data, directly or indirectly by involving teachers and staff in collecting important information, (2) Implementation of participatory decision-making in improving the quality of education is by involving the academic community of the madrasah in making a democratic and participatory policy, (3) Evaluation of participatory decision-making in improving the quality of education by reviewing problems related to the program repeatedly and re-making decisions in a participatory manner to find out the development of the program periodically.